Possible role of apoptosis in the pathogenesis and clinical evolution of radicular cyst: an immunohistochemical study. (21st January 2013) - Loreto, C.; Galanti, C.; Leonardi, R.; Musumeci, G.; Pannone, G.; Palazzo, G.; Rusu, M. C.
Abstract Aim To investigate whether the apoptotic cascade is activated through the extrinsic pathway in epithelial lining and connective tissue of radicular cysts. Methodology Fifteen radicular cysts were fixed in formalin, embedded in paraffin wax and processed for immunohistochemistry to evaluate the expression of polyclonal antibodies against Tumour necrosis factor–related apoptosis‐inducing ligand (TRAIL), DR5 and caspase‐3. Immunocomplexes were treated with the secondary antibodies and finally detected using the avidin–biotin–peroxidase complex. Immunoreactivity was visualized by development with 3, 3′‐diaminobenzidine. Data were analysed using the Mann–Whitney U‐test; P < 0.05 was considered significant. Results The three antibodies were detected in connective tissue fibroblasts of all radicular cysts; TRAIL and DR5 immunoexpression was significantly greater (P < 0.05) compared with that of caspase‐3. The three antibodies were also expressed in almost all epithelial layers and in endothelial cells of newly formed vessels. Conclusion The involvement of apoptosis in the pathogenesis of radicular cysts, demonstrated by the immunoexpression patterns of TRAIL, DR5 and caspase‐3 in lining epithelium and connective tissue, may explain their bland clinical aggressiveness and slow, benign evolution.